Development of a Visitor Management System According to The Demands of Higher College Libraries in The 4.0 Era - Suroto, Suroto (Universitas Airlangga, 2023)
ABSTRACT Recording user visits to higher education library reading rooms is an important routine activity for evaluating the function of the reading room or the intensity of user interaction with the reading room. Manually recording visits for more than 20 reading rooms that serve more than 30,000 students, 1,000 lecturers and 500 staff is far behind in this era of industrial revolution 4.0. Therefore, it is necessary to develop a website-based visitor recording system with the help of digital card scans on smartphones and integrated with databases of students, lecturers, education staff, and records in circulation services, as well as having historical records of interactions with reading rooms that have been visited. This research aims to develop a Visitor Management System for the Unesa Library (VMSUL) that suits the visitor management needs of all reading rooms at Unesa. The method used is the development method with the Waterfall model. In the work process, apart from the research team from the Unesa Library UPT, the PPTI team and application development teams from outside Unesa were also involved. The results are (1) VMSUL Application Website with user level Central Library Admin, Reading Room Admin, (2) SSO-based Electronic Library Card which can be opened by all Unesa residents via smartphone for attendance via special scanners available in all reading rooms around Unesa, (3) History of user visits available on Unesa user smartphones, and (4) number and details of visitors available at the reading room user level and central library admin. It can be concluded that the VMSUL developed at the Unesa Library UPT can function optimally according to needs in the era of Industrial Revolution 4.0. Pengembangan Visitor Management System Sesuai Tuntutan Perpustakaan Perguruan Tinggi Di Era 4.0 ABSTRAK Pencatatan kunjungan pemustaka ke ruang-ruang baca Perpustakaan Perguruan Tinggi merupakan kegiatan rutin yang penting untuk bahan evaluasi fungsi ruang baca ataupun intensitas interaksi pemustaka dengan ruang baca. Pencatatan kunjungan secara manual untuk lebih dari 20 ruang baca yang melayani lebih dari 30.000 mahasiswa, 1.000 dosen, dan 500 tendik, sudah tertinggal jauh di era revolusi industri 4.0 ini. Oleh karena itu diperlukan pengembangan sistem pencatatan pengunjung yang berbasis website dengan bantuan scan kartu digital yang ada di smartphone dan terintegrasi dengan database mahasiswa, dosen, tenaga kependidikan, dan catatan di layanan sirkulasi, serta memiliki catatan riwayat interaksi dengan ruang baca yang penah dikunjunginya. Tujuan penelitian ini untuk mengembangkan Visitor Management System Unesa Library (VMSUL) yang sesuai dengan kebutuhan manajemen pengunjung seluruh ruang baca di Unesa. Metode yang digunakan adalah metode pengembangan dengan model Waterfall. Dalam proses pengerjaannya selain tim peneliti dari UPT Perpustakaan Unesa juga melibatkan tim PPTI dan tim pengembang aplikasi dari luar Unesa. Hasil berupa (1) Website Aplikasi VMSUL dengan level user Admin Perpus Pusat, Admin Ruang Baca, (2) Kartu Perpustakaan Elektronik berbasis SSO yang dapat dibuka oleh semua warga Unesa melalui smartphone untuk presensi melalui scanner khsusus yang tersedia di seluruh ruang baca selingkung Unesa, (3) Riwayat kunjungan pemustaka yang tersedia di smartphone pemustaka Unesa, dan (4) jumlah dan detil pengunjung yang tersedia di level user ruang baca maupun admin perpus pusat. Dapat disimpulkan bahwa VMSUL yang dikembangkan di UPT Perpustakaan Unesa dapat berfungsi secara optimal sesuai kebutuhan di era revolusi industry 4.0.